Fruit and vegetable slicer / Muhammad Danish Arnizam - Arnizam, Muhammad Danish (2024)
This project introduces fruit and vegetable slicer, aiming to change the old and inefficient of manual slicing methods. The objective is to develop a device or machine that make the slicing process and enhances productivity. The project can advance precision cutting mechanisms, and user-friendly to achieve this goal. High-speed rotating blades, automatic , and cost saving are integrated into the slicer to ensure consistent and accurate slicing of fruits and vegetables. Slicing may help in the extraction of desirable constituents from raw materials easily due to its reduction in size [3] .The anticipated outcome is a neat slicer of fruit and vegetable that significantly reduces preparation time and effort while promoting kitchen safety. Additionally, the device is expected to deliver visual appealing and precise slices for culinary purposes. By improving food preparation in both professional and home kitchens, the automatic fruit and vegetable slicer has the potential to optimize productivity, creativity, and overall enjoyment in the culinary domain.